TARI PASAMBAHAN KARYA SYOFYANI : STUDI KASUS GAYA GERAK TARI - Tiara Virginia Aulia; Indrayuda Indrayuda; Herlinda Mansyur (FBS Universitas Negeri Padang, 2015)
Abstract This article airms to reveal the movement form of Pasambahan dance creation of Syofyani. Syofyani Pasambahan dance is a dance that often featured or displayed in various events, both at the local, and national and international. Type of the research refers to a qualitative research with descriptive method. Object of the research is Syofyani Pasambahan dance. Research instruments is author it self, data collected from literature study, interview, observation, and documentation. Data analyzed with Miles and Huberman model approach. Result of research found that the movement form of Pasambahan dance by Syofyani has uniqueness which combining the dance form of Minangkabau and Melayu. Part of appearance and form of movement form of Pasambahan dance by Syofyani consists of (1) posture, dorninant thing in this dance always shows pitunggu and standing position from dancers. Attitude motion shows the attitude in accordance with the rules of agility and elegance. (2) technique, shows the movement that comes from pencak silat and the art of silat. Specification or characteristic from movernent of Pasambahan dance by Syofyani lies on agility and elegance of art of silat and siganjua lalai’s move. Dance character more lyrical and flowing in a more staccato flow. Keywords : form, Pasambahan’s dance, and creation of Syofyani.